Penyelesaian Sengketa Ekonomi Syariah Melalui Proses Litigasi(Studi Penelitian Pengadilan Agama Karanganyar) - Romza, Mifro Na'imullah; , Mutimatun Ni'ami, SH., M.Hum (2020)
In the development of Islamic economics in Indonesia is not spared also by the existence of disputes or disputes, it can not be separated because the causes of Islamic economic disputes in Indonesia are very diverse, one of the causes of Islamic economic disputes is because one of the parties did not do their achievements or the so-called Default, or occurred because the parties do not understand the legal principles that govern it or the problems in interpreting the contents of the agreement (contract). Sharia economic dispute resolution is the competence and authority of the Religious Court based on the Explanation of point (1) Article 49 of Law Number 3 of 2006 concerning Amendment to Law Number 7 of 1989 concerning Religious Courts, and reaffirmed in Article 55 paragraph (1) Law Number 21 Year 2008 concerning Sharia Banking which states that if a dispute occurs in the field of sharia banking, the settlement of the dispute is submitted to the Religious Court. In this case the religious court has the right and authority to accept, try and resolve it. In the settlement of Islamic economic disputes the parties can choose to file with a regular lawsuit or a simple lawsuit, but must comply with the applicable provisions for filing the lawsuit.